Financial Fasilitation to Support Commercialization of Superior Breed Innovation - Atien Priyanti; Nur Chasanah (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
Livestock products innovation, especially of those superior breed have become one of the solution in the development of livestock production, where in reality is very limited on the availability of good quality breed. Indonesian Agency of Agricultural Research and Development through Indonesian Center for Animal Research and Development Implementing Units have been responsed these needs through breeding research started in the year of 2000. This effort have been yielded some superior local breeds, i.e. beef cattle, sheep, goats, chicken, duck and rabbit that are ready to disseminate to the community, especially for farmers. The dissemination of these superior breeds may enabling to expand and reach its distribution massively to increase animal production. One of the determinant factor to develop the process of its development is availability of financial access, which most farmers in general are very much constrained by capital asset. Therefore, facilitation support is needed to increase capital capacity that is impartial and accommodates the business characteristics. Objective of the manuscript is to review of facilitation support needed of the superior breed innovative research that disseminate to maintain sustainability of its development. In recent years, the Government has launched program of People’s Busines Credit (KUR) that could be optimized to scalling up farmers’ farming with good quality breed. Bank accessibility has demanded to have economics size of scale to be financed in order to guarantee profitable business with its liability cash flow. Meanwhile, livestock farming had been dominated by small scale farmers and yet for production oriented to reach its profitability. Supervision and technical guidance need to be consistently assisted to farmers as prospectous KUR debitor program in order to accelerate the process on disbursement of credit to supply their capital asset.